From Waste to Health: Integrating Zero Waste and Circular Economy Principles in Healthcare Sustainability - Seberíni, Andrea; Khalil, Omnia; Tokovska, Miroslava (Studia Ecologiae et Bioethicae, 2026)
Contemporary environmental and healthcare sustainability challenges have driven the evolution of zero waste systems from simple waste reduction strategies into comprehensive frameworks that prioritise public health alongside ecological protection and social equity. This transformation is critical within healthcare sustainability contexts, where environmental policy frameworks, public health imperatives, circular economy principles, and sustainable healthcare delivery must be systematically integrated. This article investigates the transformation of zero waste frameworks toward health-centred approaches and develops an integrated theoretical model through evolutionary analysis. Based on the conceptual systematic review (CSR) framework, the study employs dual analytical and prescriptive methodologies, examining theoretical developments through the systematic analysis of conceptual frameworks from economy, sustainable environments, and public health domains. Analysis reveals that zero waste frameworks have evolved through multiple pathways that incorporate health-centred approaches: reducing toxic exposures, improving infectious disease control, enhancing community wellbeing, creating economic opportunities, and promoting environmental justice. Effective implementation requires multisectoral collaboration, adaptive governance mechanisms, and inclusive community engagement for systemic transformation. The proposed integrated theoretical framework leverages evolutionary insights to guide the development of zero-waste systems that simultaneously prioritise health protection while advancing sustainability dimensions.